Effects of Management Related Practices on Turkey Hen Performance Supplemented With Either Original XPC™ or AviCare™ - Bartz, Brooke M.; McIntyre, Don R.; Grimes, Jesse L. (Frontiers in Veterinary Science, 2018)
During commercial production, turkeys may be exposed to several different types of stressors related to environmental conditions and management practices. Historically, antibiotics have been used to aid in the alleviation of the impacts of stressful situations, and alternatives to antibiotics related to reducing stress are being researched. This study consisted of three rearing trials and had two objectives: (1) Investigate the effects of common U.S. turkey production practices, including environmental and management induced stress, on turkey hens grown to 63 days, and (2) Determine the response of stressed birds to dietary supplementation with fermentation derived functional metabolites. Treatments consisted of a positive control (stressed but not supplemented), a negative control (non-stressed and not supplemented) and two treatment groups that were stressed and supplemented with different products (Original XPC™ or AviCare™). Supplemental products were administered in a dry (feed) and liquid (drinking water) form, and consisted of fermentation derived functional metabolites. Products were evaluated on their effectiveness to mitigate stress responses and turkey performance. Birds were exposed to some combinations of the following stressors: feed and water withdrawal, cold, heat, and crowding. Although the stressors in this study were applied for less than 24 h, they produced significant physiological responses. Blood corticosterone levels, measured immediately after stress, were significantly higher in positive control birds than in negative control birds. In addition, stressed birds had reduced body weights and increased FCR after stress. Stressed birds, supplemented with products had mixed, but generally positive response as measured by bird performance. Based on the response to stress, as observed by alterations in blood corticosterone levels and differences in performance between the two control groups, researchers induced an effective stress model. The use of supplementary products consisting of fermentation derived functional metabolites shows promise for reducing negative impacts of a mixture of stressors.